#sorrynotsorry: A Well-meaning Response to PTJ1. (June 2015) - Salter, Mark B.
Responding to Patrick T. Jackson's 'Must International Studies Be a Science?' I argue that his proposed division of incommensurable logics of inquiry (aesthetic, normative, empirical and technical) cannot be separated in a meaningful way in the exercise of judgement, and that corporeal and practical skill must be also included.